The Introduction of Long-term Care Insurance (LTCI) in China and Lessons from the Policy in South Korea: Focusing on the LTCI Pilot Programs of Shandong Province in China - 김근홍; 맹상기; 강은희; 서경원; 이송희; 이순덕 (Korean Journal of Social Quality, 2021)
China implemented the one-child policy in 1979 and has experienced its various negative effects since then. In particular, the social phenomenon during the transition of its society to an aging one is a representative example of the negative effects. During its transition to an aging society, China has been in a situation where it has had to deal with problems related to the elderly and family support that some East Asian countries such as Japan and South Korea has also experienced. With this as background, this study tried to focus on long-term care insurance for the elderly as an institutional solution for solving various problems that arose during its transition to an aging society. Specifically, the introduction process of long-term care insurance system for the elderly in China was examined, and some implications were obtained from the policies in South Korea, which is known as an advanced country regarding this system. Through various related literature and prior research, the study summarized the background to the introduction of the long-term care insurance system for the elderly in China, the progress of the trial program of the long-term care insurance system for the elderly in China, the expansion of the trial program, and implications of the long-term care insurance system for the elderly in South Korea. The implications of this study are as follows: First, this research is significant in that it will show how the pilot operation of China's long-term care insurance system flowed along with basic related data. Second, it is meaningful as South Korea’s long-term care insurance system was explored as an institutional way to address problems related to providing support for the elderly in China. KCI Citation Count: 0